2020
DOI: 10.1016/j.bjpt.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reducing anterior pelvic tilt on shoulder posture and the electromyographic activity of scapular upward rotators

Abstract: Background: Modifications of posture in a segment may influence the posture of adjacent and nonadjacent segments and muscular activity. The spine-shoulder and spine-pelvis relationships suggest that the pelvis may influence shoulder posture. Objective: To investigate the effect of the active reduction of the anterior pelvic tilt on shoulder and trunk posture during static standing posture and on the electromyographic activity of the scapular upward rotators during elevation and lowering of the arm. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…This is in accordance with the results obtained when using the swivel seat for paddling: while its use influenced the rotation angles between the pelvis and the trunk, the upper limb kinematics were less affected by the choice of the seat (Fohanno et al, 2011 ; Willmott and López-Plaza, 2014 ). It is also in accordance with the analysis from Murta et al ( 2020 ), who reported the impact of a pelvic mobility reduction on the trunk kinematics but not on the shoulder kinematics. The significant differences observed for the glenohumeral plane of elevation dof were limited to a couple of degrees (<10°) and for limited time periods (compared to the pelvis and trunk significant differences).…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with the results obtained when using the swivel seat for paddling: while its use influenced the rotation angles between the pelvis and the trunk, the upper limb kinematics were less affected by the choice of the seat (Fohanno et al, 2011 ; Willmott and López-Plaza, 2014 ). It is also in accordance with the analysis from Murta et al ( 2020 ), who reported the impact of a pelvic mobility reduction on the trunk kinematics but not on the shoulder kinematics. The significant differences observed for the glenohumeral plane of elevation dof were limited to a couple of degrees (<10°) and for limited time periods (compared to the pelvis and trunk significant differences).…”
Section: Discussionsupporting
confidence: 92%
“…Active motion is required to build the stability of the scapula on the chest wall, and the pelvis position in the anterior pelvic tilt has a direct effect on the biomechanics of the upper limbs, causing the external rotation of the humerus (Appel, Mayston, & Perry, 2011;Griffin, & Bernhardt, 2006;Hanger, et al, 2000;Hayner, 2012;Murta, et al, 2020;Pandian, et al, 2013;Turner-Stokes, & Jackson, 2002). Complementing, the same authors point out a conflict between the evidence of the use of the neuromuscular bandage to reduce pain, function or even the upper limb range of motion (Griffin, & Bernhardt, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…the evidence related to the activity and participation is insufficient (Appel, Mayston, & Perry, 2011;Grampurohit, Pradhan, & Kartin, 2015); Griffin, & Bernhardt, 2006;Hanger, et al, 2000;Hayner, et al, 2012;Hsieh, et al, 2021;Huang, et al, 2016;Mota, & Silva, 2014;Murta, et al, 2020;Pandian, et al, 2013;Turner-Stokes, & Jackson, 2002;Yang, L., Yang, J., & He, 2018). Pain was measured in two different manners in the included studies: through pain intensity and number of days without pain.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in pelvic tilt have been found to influence the muscle activation during assessment and common exercises at not only the hip and pelvis, [36][37][38] but also the lumbar spine 39 and even the shoulder girdle. 40…”
Section: The Relationship Between Pelvic Tilt Hip Function and Pathologymentioning
confidence: 99%